The Power of Sorghum Farmer Corporation as Strengthening National Food Security - Susanti, Ari (Jurnal Penelitian IPTEKS, 2024)
The cultivation and development of sorghum plants is the government's effort in strengthening national food security. Sorghum can substitute wheat where Indonesia is the world's largest wheat importer as much as 10-11 million tons a year. The acceleration of sorghum cultivation is carried out by the government by cooperating with appointed private parties, one of which is PT H2O (Holistic Health business Opportunity) Group Indonesia. In its idea, PT H20 developed a farmer-based sorghum farming area with a pilot project in the Semarijo Area (Sumberjati Village, Rejosari Village, Manting Village and Jembul Village), Pacet District, Mojokerto Regency. Farmer Corporation is one of the government's efforts in improving the welfare of farmers as stated in Minister of Agriculture of the Republic of Indonesia regulation No. 18/Permentan/RC.040/4/1018. This research aims at farmer corporations developed by PT H2O Group Indonesia from the aspects of management and communication established with its stakeholders. The research method used is qualitative descriptive to obtain as much data as possible with data collection techniques through in-depth interviews and field observations for 3 months. The result is the development of farmer corporation-based agricultural areas carried out by PT H2O Group Indonesia (Holistic Health business Opportunity) is (1) unique, solid and controlled internal management, (2) establishing effective communication of all stakeholders by establishing mutualist partnerships (3) this farmer corporation is able to empower the community and the development of agricultural areas can go hand in hand so as to improve the welfare of sorghum farmers. Thus, this system is able to improve the welfare of farmers and Indonesia is able to be self-sufficient in food and enter the international market